Inclusive technology enhanced learning overcoming cognitive, physical, emotional, and geographic challenges - Passey, Don (Routledge, 2014)
"Inclusive Technology Enhanced Learning draws together a remarkable breadth of research findings from across the field, providing useful data on the power of technology to solve cognitive, physical, emotional or geographic challenges in education. A far-ranging assessment, this book combines research, policy, and practical evidence to show what digital technologies work best for which learners and why. Inclusive Technology Enhanced Learning takes a number of unique perspectives, looking at uses of digital technologies through a detailed learning framework; considering different groups of users and how they can be individually supported through digital technologies; and exploring how those who support different categories of learners can apply technologies to their specific support needs. This powerful meta-analysis of research on technology enhanced learning will be invaluable reading for anyone concerned with the impacts of digital technologies on learning across subject areas, age ranges, and levels of ability"--Provided by publisher.